'Fiction keeps memory about the war alive': Mnemonic migration and literary representations of the war in Bosnia. (August 2022) - Ortner, Jessica; Sindbæk Andersen, Tea; Wierød Borčak, Fedja
This article investigates how literary works of fiction depicting wartime memories from Bosnia were received by groups of lay readers in Copenhagen, Manchester and Berlin. We introduce the concept of mnemonic migration to include both the narrative strategies employed by migrant authors in order to represent such memories in new mnemonic contexts, and the reception of this type of literature in different social and cultural settings. By investigating readers' reactions to literature by migrants who write about topics related to own or fictional experiences in wartime Bosnia, we explore literature as a medium that makes memories travel and has the potential to create prosthetic memories. Studying what happens in the encounter between the texts and recipients within the following three national communities of remembrance – Denmark, Germany and England – we ask if the texts are capable of representing Bosnian wartime memories in an emotionally appealing manner that urges the reader to incorporate them into their own stock of memories. Based on focus group interviews in the three cities, we argue that the agency of literature in transmitting memories into new frameworks is limited but definitely present. We found that the literary style of memory mediations was an important factor and many readers preferred texts with more clarity and factuality. Nevertheless, in spite of the frustration experienced by a significant group, most readers felt emotionally engaged by at least parts of the texts. We observed that there were considerable differences in how readers in the three social settings related to the events. However, in all three countries, differences between generational groups most obviously affected the readings. Often, the books made readers aware of the limited role of the Bosnian War in their respective public frameworks of memory and created a wish for a more thorough commemoration of that event.